1.2x(x-2)=-x

Simple and best practice solution for 1.2x(x-2)=-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.2x(x-2)=-x equation:


Simplifying
1.2x(x + -2) = -1x

Reorder the terms:
1.2x(-2 + x) = -1x
(-2 * 1.2x + x * 1.2x) = -1x
(-2.4x + 1.2x2) = -1x

Solving
-2.4x + 1.2x2 = -1x

Solving for variable 'x'.

Reorder the terms:
-2.4x + x + 1.2x2 = -1x + x

Combine like terms: -2.4x + x = -1.4x
-1.4x + 1.2x2 = -1x + x

Combine like terms: -1x + x = 0
-1.4x + 1.2x2 = 0

The solution to this equation could not be determined.

See similar equations:

| 10y+6x=12 | | 2a-7=3a+a+11 | | (40+98+94+102+21+x)/6=88 | | 5+3(s-5t)= | | 19b-9b=35 | | 14v-9b=35 | | 1000+x(10)=2000 | | 3y-2x=3 | | 8.9*10= | | -6x+24=24-9x | | 3(x+2)=32 | | (t-3)2-(t-2)2=5 | | (2x-1)*x=91 | | 70+2m=24m^2 | | 2+a=3(6a-5) | | (2x^2)-4x-30=0 | | (2x-1)x=91 | | r^2+9=6r | | 305+x(5)=350 | | 5x=-37 | | 10=-2x+8 | | 1x+15=25+12x | | -50=19+x | | x+6=-5x+5x | | -7+5=12 | | 6x+42-13x=24 | | x^2+16x+64=-9 | | 7(3x+9)-6(2x+5)= | | 6240000/100= | | 2800+x(150.99)=5819.80 | | -8(2x-4)+7(3+5x)= | | b+3=b*3 |

Equations solver categories